Evaluation of the potential of Neurofeedback for the obesity treatment according to the literature data - Ziyasheva А.М.; Datkhabayeva, G.K. (Fundamental and Experimental Biology, 2022)
The article is devoted to the evaluation of prospects of applying the technology of self-regulation of the brain functional state by means of biofeedback using EEG parameters (Neurofeedback) in the obesity treatment — chronic disease, the prevalence of which has reached the scale of a global epidemic. It serves as a serious risk factor for cardiovascular diseases, certain types of cancer, type II diabetes, as well as other chronic non-communicable and infectious diseases, including severe COVID-19 and its complications. The essence of biofeedback technology is constituted in training the subject’s ability to voluntary control certain physiological parameters of own body to bring them to optimal scores which correspond to the healthy functioning of the body for improving health and performance. The development of self-regulation ability through biofeedback is based on the precise instrumental measurements of physiological activity indicators, such as brain activity, the activity of cardiovascular and respiratory systems, muscle activity, and skin temperature. The article provides a neurobiological justification of the expediency and effectiveness of neurofeedback in the obesity treatment; highlights the protocols used for the biofeedback therapy of obesity and associated disturbances of eating behavior; emphasizes the importance of neurofeedback therapy for optimizing brain activity patterns by voluntary neuromodulation, restoring the neurodynamic balance of regulatory systems for driving the subject into a stable state of calm and psychological comfort without resorting to unhealthy food.